1992
DOI: 10.2337/diab.41.10.1221
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology of Stimulus-Secretion Coupling in Human β-Cells

Abstract: Herein, we review the applicability to human beta-cells of an electrophysiologically based hypothesis of the coupling of glucose metabolism to insulin secretion. According to this hypothesis, glucose metabolism leads to the generation of intracellular intermediates (including ATP), which leads to closure of ATP-sensitive K+ channels. Channel closure results in membrane depolarization, the onset of electrical activity, and voltage-dependent Ca2+ entry. The resultant rise in cytosolic Ca2+ leads to Ca(2+)-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
116
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 0 publications
10
116
0
Order By: Relevance
“…Although models of human β-cells exist 50,72,73 which capture the different electrophysiological properties of these cells compared to rodent β-cells 50,72-75 , there is large variability in the quality, function and donor details of human islets. 76-78 Furthermore, the data that these models are based on uses recordings from dispersed human β-cells that were cultured in media without the addition of any serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although models of human β-cells exist 50,72,73 which capture the different electrophysiological properties of these cells compared to rodent β-cells 50,72-75 , there is large variability in the quality, function and donor details of human islets. 76-78 Furthermore, the data that these models are based on uses recordings from dispersed human β-cells that were cultured in media without the addition of any serum.…”
Section: Discussionmentioning
confidence: 99%
“…50,73,74 It has subsequently been shown that supplementation of islets with serum is essential for preserving islet function. 79 Given that human β-cells are known to burst, 75,80-83 and that the Cha-Noma model generates bursting dynamics, we opted to use the Cha-Noma model as a reliable proxy for a human β-cell in our models of human islets. This also afforded a direct comparison of the influence of islet architecture between mouse and human.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, insulin activation of the pancreatic transcription factor PDX-1 is independent of K ATP channel-mediated membrane excitability (43), suggesting a possible role for intracellular Ca 2ϩ stores. Although both the production and secretion of hormones are dependent on calcium at several levels (9,35,44), insulin biosynthesis and secretion are not always coupled (45). In dispersed human islet cells, exogenous insulin did not stimulate c-peptide secretion in either resting or high glucose (Fig.…”
Section: Naadp-sensitive Camentioning
confidence: 99%
“…These results indicate that NAADP acts on Ca 2ϩ stores relatively distinct from those modulated by ryanodine and xestospongin in this cell type with a pharmacological profile similar to that of insulin. Interestingly, NAADP-stimulated Ca 2ϩ release can be inhibited by voltage-gated Ca 2ϩ channel antagonists (34), which are potent suppressors of Ca 2ϩ signaling in human beta cells (35).…”
Section: Naadp-sensitive Camentioning
confidence: 99%
“…Pancreatic beta cells have evolved as master regulators of metabolic homeostasis, sensing glucose and other nutrients and releasing appropriate insulin to induce their storage. We understand the basics of beta cell biology, especially the ionic mechanisms underlying insulin release in response to large and abrupt glucose stimuli, which include a rapid rise in cytosolic Ca 2+ subsequent to the metabolismdriven closure of K ATP channels, as well as a plethora of coupling factors [4]. However, we do not understand precisely how human beta cells respond to physiological stimuli and make fate decisions.…”
mentioning
confidence: 99%